Pengembangan Modul Pembelajaran Fisika Berbantuan PheT Berbasis Inkuiri Pada Materi Usaha dan Energi Kelas X SMA Negeri 1 Gerung Lombok Barat - Wandira, Ayu; Bahtiar; Ali, Lalu Usman; Septiana, Yolanita (CAHAYA: Journal of Research on Science Education, 2023)
This study aims to determine the validity of the development of inquiry-based phet-assisted physics learning modules on effort and energy material according to media experts at SMA Negeri 1 Gerung, and to determine the validity of the development of inquiry-based phet-assisted physics learning modules on effort and energy material according to material experts at SMA Negeri 1 Gerung. The research instrument used is a validation questionnaire for material experts, media experts, teachers, and student responses using small group trials and large group trials in class X IPA. This research was conducted at SMA Negeri 1 Gerung West Lombok majoring in Science This research is a Research and Developmend (R&D) model developed in this study is ASSURE, this ASSURE model uses 6 stages, namely: (1) Analyse Learners, (2) State Objectives, (3) Select Strategy, Technology, Media, and Materials, (4) Utilise Technology, Media and Materials, (5) Require Learner Participation, (6) Evaluate and Revise. The results of this study are the Physics Learning Module from material experts obtained a percentage value of 75.58% with a category worth using, the assessment of media experts obtained a percentage value with a category, for the assessment of the Sma Negeri 1 Gerung teacher obtained a percentage value of 82.24% with a category agreeing to be used in the school, and for the assessment of small groups and large groups obtained a percentage value of 85% and 88% categorised as a conclusion: Inquiry-based Phet-assisted Physics Learning Module is feasible to use, effective and active to use as Physics Learning Module.